2015
DOI: 10.1007/s00038-015-0763-y
|View full text |Cite
|
Sign up to set email alerts
|

Electronic cigarette use among Korean adults

Abstract: E-cigarette use was strongly associated with conventional cigarette use and with frequent heavy drinking. Dual use e-cigarettes and conventional cigarette use as well as the association between heavy alcohol use and e-cigarettes need further exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 23 publications
3
22
1
Order By: Relevance
“…This study, similar to previous studies [5,23,24], found that e-cigarette use was more prevalent among ever conventional cigarette smokers than among never conventional cigarette smokers. In addition, as the frequency and intensity of cigarette smoking increase, the percentage of frequent use of e-cigarette increases.…”
Section: Discussionsupporting
confidence: 92%
“…This study, similar to previous studies [5,23,24], found that e-cigarette use was more prevalent among ever conventional cigarette smokers than among never conventional cigarette smokers. In addition, as the frequency and intensity of cigarette smoking increase, the percentage of frequent use of e-cigarette increases.…”
Section: Discussionsupporting
confidence: 92%
“…Most Hong Kong residents (83.8%) had heard about e-cigarettes. The prevalence of ever use of e-cigarettes (2.3%) [ 31 ] was similar to Taiwan (3%) [ 32 ] and China Mainland (3.1%) [ 33 ], but lower than many other countries (>6%) [ 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Previous studies suggested that the low prevalence may be due to the less aggressive e-cigarette promotion than western countries [ 31 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…showed a pooled prevalence of current e-cigarette users of 11.1% (Xu et al 2016). However, a lower prevalence of current e-cigarette users was observed in Asia-Pacific countries ranging from 0.8 to 1.3% (Lee et al 2016;Tabuchi et al 2016;Li et al 2015). In Malaysia, e-cigarette made its debut about 10 years ago.…”
Section: Abstrakmentioning
confidence: 99%